Too long in the bush - Beadell, Len, 1923-1995. (Adelaide [S. Aust.] : Rigby, 1965)
Story of how author made the first road ever to cross Central Australia; Account of Warburton Mission and natives life there; Mention of Aboriginal groups met on journey.
Keywords: Roads -- Australia, Central -- Design and construction; Roads -- Australia, Central; Transport - Road - Construction and maintenance; Australia, Central -- Description and travel; Gunbarrel Highway (W.A.); Milyirrtjarra / Warburton (Central WA SG52-09); South Australia - Central Australia (SA SG52, SG53)